Differences in psychometric characteristics of outpatients with somatic symptom disorder from general hospital biomedical (neurology/gastroenterology), traditional Chinese medicine, and psychosomatic settings - Ma, Dandan; Lu, Wei; Fritzsche, Kurt; Toussaint, Anne Christin; Li, Tao; Zhang, Lan; Zhang, Yaoyin; Chen, Hua; Wu, Heng; Ma, Xiquan; Li, Wentian; Ren, Jie; et al. (Frontiers in Psychiatry, 2023)
The aim of this study is to investigate the psychometric characteristics of outpatients diagnosed with somatic symptom disorder (SSD) in biomedical, Traditional Chinese Medicine (TCM) and psychosomatic settings.A total of 694 participants who completed SCID-5 and questionnaires were presented in our former study, as 3 of them had missed questionnaire data, a total of 694 participants are presented in this study. A secondary analysis of the psychometric characteristics of Somatic Symptom Disorder-B Criteria Scale (SSD-12), Somatic Symptom Severity Scale of the Patient-Health Questionnaire (PHQ-15), Patient Health Questionnaire-9 (PHQ-9) and General Anxiety Disorder-7 (GAD-7) is done to compare differences among outpatients from the three settings of medical specialties.Results: Based on the DSM-5 criteria, 90 out of 224 (40.2%) participants enrolled in biomedical departments (represented by neurology and gastroenterology departments), 44/231 (19.0%) in TCM departments, and 101/239 (42.3%) in the psychosomatic medicine departments were diagnosed with SSD. The scores of PHQ-15 in the biomedical, TCM and psychosomatic settings were 11.08 (± 4.54), 11.02 (± 5.27) and 13.26 (± 6.20); PHQ-9 were 10.43 (± 6.42), 11.20 (± 5.46) and 13.42 (± 7.32); GAD-7 were 8.52 (± 6.22), 9.57 (± 5.06) and 10.83 (± 6.24); SSD-12 were 22.26 (± 11.53), 22.98 (± 10.96) and 25.03 (± 11.54) respectively. The scores of PHQ-15, PHQ-9 and GAD-7 in SSD patients were significantly higher in psychosomatic departments than that in biomedical settings (p < 0.05).The cutoff point for SSD-12 was ≥16 in total patients; 16, 16, 17 in biomedical, TCM and psychosomatic settings, respectively. The cutoff point for PHQ-15 was found to be ≥8 in total patients; 8, 9, 11 in biomedical, TCM and psychosomatic settings, respectively.Conclusions: SSD patients from psychosomatic departments had higher level of somatic symptom severity, depression and anxiety than from TCM and biomedical settings. In our specific sample, a cutoff point of ≥ 16 for SSD-12 could be recommended in all three settings. But the cutoff point of PHQ-15 differs much between different settings, which was ≥8, 9, and 11 in biomedical, TCM, and psychosomatic settings, respectively.